Restoration of an endodontically treated molar taurodont: A 3-year follow-up case - Antoniadou Maria; Malivitsi Christina; Margeti Zoi; Eleutherios-Terry Farmakis (Wolters Kluwer Medknow Publications, 2015)
Taurodontism is an anomaly or variation of the anatomy of the tooth basic shape, characterized by an enlarged pulp chamber, apical displacement of the pulpal floor, and no constriction at the level of the cement-enamel junction. Due to these characteristics, endodontic treatment and restoration of these teeth is extremely challenging. In this paper, a review of the phenomenon and prevalence of taurodontism is carried out, and interesting clinical case is described in terms of endodontic notification and final crown restoration. In order to achieve longevity, by preventing microleakage, the final restoration is considered provocative, concerning the selection and combination of restorative materials to be used in such cases. Special care should always be given in occlusion and cuspal protection.